Computational exploration of the reaction mechanism of the Cu+- catalysed synthesis of indoles from N-aryl enaminones - Bernardo, Carlos E. P. (2016)
We have studied the role of Cu+-phenantroline as a catalyst in the cyclization of N-aryl-enaminones using density-functional theory computations. The catalyst was found to bind the substrate upon deprotonation of its eneaminone, and to dramatically increase the acidity of the carbon adjacent to the ketone functionality. The deprotonation of this carbon atom yields a carbanion which attacks the aryl moiety, thereby closing the heterocycle in the rate-determining step. This C–C bond forming reaction was found to proceed much more rapidly when preceded by re-protonation of the substrate N-atom (which had lost H+ in the initial step). Hydride transfer to the catalyst then completes the indole synthesis, in a very fast step. The influence of Li+ and K+ on the regioselectivity of the cyclization of bromo-substituted analogues could not, however, be reproduced by our model. Alternative pathways involving either single-electron transfer from the catalyst to the substrate or ring cyclization without previous carbon α-deprotonation were found to be kinetically or thermodynamically inaccessible.